Polysaccharide-based composite coating formulations for shelf-life extension of fresh banana and mango - Kittur, F. S.; Saroja, N.; Tharanathan, R. N.; Mathooko, F. M (Orgz, 2001)
The effects of four different composite coating formulations based on polysaccharides on maintaining quality and an extended shelf-life of banana and mango at 27±2 °C were investigated and compared with commercial Waxol-coated and uncoated fruits. The formulations consisted of modified starch, cellulose and chitosan, blended with a suitable lipid component and a wetting agent. Quality parameters measured included firmness, total soluble solids and titratable acidity. Physiological parameters measured were CO2 evolved and weight loss due to respiration and transpiration. The polysaccharide-based coatings displayed retarded colour development, lower acidity and greater firmness values compared to Waxol and control. CO2 evolution and loss in weight were also reduced significantly. The data were also subjected to PCA, to differentiate the characteristics of the five types of films. Chitosan-based coatings were much superior in prolonging the shelf-life and quality of banana and mango.
Keywords: Chitosan; Starch; Cellulose; Coating formulations; Shelf-life